IMPLEMENTASI DATA MINING K-NEAREST NEIGHBOR PADA PENERIMAAN KARYAWAN DI PT DWI SUMBER ARCA WAJA - Saputra, Ega; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2022)
Recruitment is the first step taken by PT. Dwi Sumber Arca Waja (PT DSAW) to recruit prospective professional workers. Professionalism is needed as one of the inputs to produce the appropriate output. PT DSAW is a Large Steel manufacturing company that acts as a supplier that provides goods to support the oil and gas sector. The Head Office is located on Jl. Hang Kesturi I No.8, Kawasan Industrial Estate, Batam. Over time, PT. DSAW needs to find a way to be faster and more efficient in determining prospective employees so that they can quickly find suitable and appropriate employees. This study aims to apply the KNearest Neighbor (K-NN) classification method to the recruitment selection system at PT DSAW. The K-NN method will calculate the level of similarity by measuring the distance between the needs set by PT. DSAW with data held by prospective employees. Furthermore, the K-value is taken from applicants who have a similarity value of 80%. Applicants who have the same score of 80% will be included in the next test.